Rising Inequalities Between the Richest and the Poorest - Rameli, Norizan; Dani Salleh, (Human Sustainability Procedia, 2023)
In many countries, income and wealth inequalities has increased in recent decades including Malaysia. Rising inequalities, as well as related disparity and fears, have fueled social discontent and constitute the primary driver of today's heightened political division. A more unequal society can diminish trust in public institutions and democratic governance. Global inequalities are threatening geopolitical stability. Rising inequality has become as a prominent political debate topic and public policy concern.